Incremental value of global longitudinal strain in long-term risk prediction after acute coronary syndrome. A SWEDEHEART registry based echo study. (3rd October 2022) - Lenell, J; Lindahl, B; Erlinge, D; Spaak, J; Jernberg, T; Baron, T
Abstract: Background: Global longitudinal strain (GLS) by 2D speckle tracking echocardiography has emerged as a new method for assessing left ventricular (LV) function, however its added value in long-term risk prediction after Acute Coronary Syndrome (ACS) has not been clearly established. This study aimed to investigate GLS as a predictor of death and heart failure re-hospitalization after ACS in relation to more established echocardiographic measures. Method: 1385 consecutive patients with acute coronary syndrome (47% STEMI, 45% NSTEMI, unstable angina 3.6% and unspecified ACS 4.5%), admitted between 2008 and 2014 to the three participating Swedish university hospitals were reported to the SWEDEHEART registry and underwent routine echocardiography during their hospital stay. The echo data was retrospectively collected from each study site and reviewed at a Core Lab. The prognostic value of systolic left ventricular function parameters (LVEF and GLS) regarding all-cause mortality and heart failure (HF) hospitalizations (median follow-up 6.8 years) was studied using the Cox proportional Hazards model. A nested model comparison was performed with C-statistics. Results: In the 942 patients remaining after exclusion (median age 65 years, 77% men) median LVEF was 55% (inter quartile range (IQR) 47–60) and median GLS −14.8% (IQR −17.8–11.8). The combined endpoint of HF hospitalization and all-cause death was reached in 17.7% of the patients, 12.1% of the patients died and 8.7% were re-admitted due to HF. After adjustment for baseline characteristics, both LVEF and GLS were individual independent predictors of the combined endpoint, HR 0.964 (95% CI 0.949–0.980, p<0.001) and HR 1.042 (95% CI 1.002–1.084, p=0.042) respectively. The C-statistics increased from 0.752 (95% CI 0.712–0.792) to 0.755 (95% CI 0.706–0.785) when GLS entered the model with clinical data and LVEF. Conclusion: In a large cohort of patients with ACS and normal or near-normal ejection fraction, GLS emerged as an independent long-term risk predictor of all-cause mortality and heart failure hospitalizations. The incremental predictive value of GLS on top of clinical background and LVEF was statistically significant, but of limited clinical significance. Funding Acknowledgement: Type of funding sources: None.